The Influence of Ice Breaking Technique Concentration on Studying Indonesian Language Subjects for Class IV Students at Al Hadi Integrated Islamic Elementary School - Harum Candra Dri Wulan Sakti; Alfian Eko Rochmawan; Muhammad Fatchurrohman (CV. Creative Tugu Pena, 2024)
The research objectives of this study are 1) To find out how high the learning concentration value is in the Indonesian Language subject of class IV of Al Hadi Integrated Islamic Elementary School in the 2024/2025 academic year, 2) To find out how high the use of ice breaking techniques can be implemented in class IV of Al Hadi Integrated Islamic Elementary School in the 2024/2025 academic year, 3) To find out how much influence the ice breaking technique has on the learning concentration of the Indonesian Language subject of class IV of Al Hadi Elementary School in the 2024/2025 academic year. The method used in this study is a quantitative method with a Descriptive Correlational Analysis approach. This withdrawal method uses a random sampling technique with a total of 44 students as respondents. Data collection techniques using questionnaires and documentation. The results of this study indicate that: 1) The concentration value of learning Indonesian is in the